2016
DOI: 10.3389/fpsyg.2016.01396
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Number and Presentation Order of High-Constraint Sentences on Second Language Word Learning

Abstract: This paper presents the results of an experiment that investigated the effects of number and presentation order of high-constraint sentences on semantic processing of unknown second language (L2) words (pseudowords) through reading. All participants were Chinese native speakers who learned English as a foreign language. In the experiment, sentence constraint and order of different constraint sentences were manipulated in English sentences, as well as L2 proficiency level of participants. We found that the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Results showed that the meaning of the novel words could be acquired in high constraint sentences but not in low constraint sentences, suggesting that high sentence constraint facilitates the acquisition of L2 contextual word meaning. This facilitation effect of high sentence constraint was also demonstrated in another study (Ma et al, 2016 ).…”
Section: Introductionsupporting
confidence: 81%
“…Results showed that the meaning of the novel words could be acquired in high constraint sentences but not in low constraint sentences, suggesting that high sentence constraint facilitates the acquisition of L2 contextual word meaning. This facilitation effect of high sentence constraint was also demonstrated in another study (Ma et al, 2016 ).…”
Section: Introductionsupporting
confidence: 81%
“…It is estimated that an L2 learner needs to know at least 35,000 words in order to understand authentic written texts (Nation, 2001). This draws the attention of many researchers, who have investigated the mechanism of L2 word learning using different methods, for example, deliberate learning method (Elgort, 2011; Ghazi Saidi et al, 2013; Perfetti et al, 2005) or incidental learning method (Bordag et al, 2015; Elgort & Warren, 2014; Ma et al, 2016; Pellicer‐Sanchez & Schmitt, 2010). These studies have centered on unambiguous words, that is, the establishment of a single form‐meaning mapping relationship.…”
Section: Introductionmentioning
confidence: 99%
“…The participants recruited in the current study were adults which may rely on both taxonomic and thematic relations. Third, there has been evidence for the modulation of sentential constraint and L2 proficiency level on L2 word learning ( Pulido, 2003 ; Borovsky et al, 2010 ; Elgort et al, 2015 ; Ma et al, 2015 , 2016 ; Chen et al, 2017 ). Only in highly constraining sentences could the meaning of L2 novel words be derived ( Ma et al, 2015 ), and higher-proficiency L2 learners outperformed than lower-proficiency L2 learners ( Ma et al, 2015 ; Chen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%